The Efficacy of External Rotation Method for The Reduction of Acute Anterior Shoulder Dislocation With and Without Greater Tuberosity Fracture - Gnawali, Gopal Prasad; Dhakal, Indra; Khatri, Kishor; Sharma, Shanta (Birat Journal of Health Sciences, 2018)
Introduction: Several methods of reduction technique have been described for the anterior dislocation of shoulder but none technique is said to be ideal. The aim of this study was to show the efficacy of external rotation method which could be safe and painless method for the reduction of the acute anterior shoulder dislocation with or without fracture of the greater tuberosity and to search the cause of failure of reduction. Objective: Objective of this study was to assess the efficacy of the external rotation method for reduction of acute anterior shoulder dislocation and to find the cause of failure of reduction. Methodology: All cases of anterior dislocation encountered in emergency department reduced by external rotation method by consultant orthopedic surgeon using basic emergency setting for resuscitation were included in the study. Fifty cases of shoulder dislocation was treated by this method and prospective evaluation done with regard to type of dislocation, the effectiveness of the procedure in achieving reduction, the need for pre-medication, the ease of performing reduction and complication if any. Results: Out of 50 cases, successful reduction was achieved in 42 patients. Premedication was not required in 36 successful reduction. Average time of reduction was 2 minutes in 30 patients and 5 minutes in 8 patients. Four Patients complained severe pain during reduction process. This method was not successful in 8 patients 2 of whom had displaced greater tuberosity fracture. Conclusion: The external rotation method is reliable and safe method for the reduction of acute anterior shoulder dislocation which can be performed relatively with less pain for both subcoracoid and subglenoid dislocation provided there is no displaced fracture of the greater tuberosity. BJHS 2018;3(2)6: 408-412.